Human Rights Mechanisms in Small Pacific States: Implications for Dialogue about Regional Human Rights Mechanisms - Liddicoat, Joy (Victoria University of Wellington Law Review, 2009)
This article draws on research conducted by the New Zealand Human Rights Commission and the Pacific Islands Forum Secretariat in regard to opportunities and challenges for national human rights mechanisms in small Pacific states. The author uses this research to highlight some of the issues and concerns in regards to the development of a regional human rights initiative. Suggestions are provided for the process to be used when engaging in dialogue regarding the implementation and development of a regional human rights mechanism.